Efeito residual da mistura glifosato e 2,4-D em milho segunda safra em solos de diferentes texturas - Gomes, Schaianne Alves (2015)
Currently, to increase the efficiency in the control of weeds it is common the use in the desiccation of a mixture of glyphosate herbicide and 2,4-D. This paper aimed to evaluate the residual effect these two herbicides about the development of corn plants, in soils of different textures. The experiment was conducted in a greenhouse in a completely randomized design in a factorial 2x2x7, 2 soil (Red-Yellow Latossol and Quartzarenic Neossol), 2 soybean desiccation times (5 and 10 days before sowing corn) and 7 treatments (recommended dose (RD) of glyphosate; RD of 2,4-D; 2, 10 and 50 times the recommended dose in blend; and one witness), with 4 replications. After emergence of corn plants, were evaluated the following characters: phytotoxicity, plant height, chlorophyll a and chlorophyll b, humid and dry mass of shoot and root. In general way, there was lesser residual effect in the Red Yellow Latossoll in all the herbicides doses and in the interval of 10 days between the desiccation and the sowing. With increased of the doses of herbicides also rose the damage caused by residual in the soil on corn plants. However, they showed good recovery throughout its development.